Is China challenging the US in the Persian Gulf? Oil, security, and politics - Lars Erslev Andersen; Yang Jiang (Danish Institute for International Studies (DIIS), 2014)
In this new report DIIS researchers Yang Jiang and Lars Erslev Andersen explore the changing strategic roles of the USA and China in the Persian Gulf region, in particular in view of US (mis)handling of local conflicts and China's expanding economic interest there, in order to identify the implications for Danish Middle East Policy. While the US has provided the security umbrella in the region, its handling of ethnic conflicts and civil wars has irritated members of the Gulf Cooperation Council (GCC). Political developments, including 9/11 and the Arab Spring, have forced the member states of the GCC to take action to avoid the spread of democratic movements and reforms, while seeking to handle their own affairs without interference from the US, EU and UN. Problems in GCC-US relations also make GCC states look Eastwards for new partners, providing a power vacuum and opportunity for China to edge in. China has expanding economic involvement in the Gulf and has overtaken the US as the biggest importer of oil from the GCC. With expanding trade, investment and contract work in the Gulf, China seeks to protect its assets and citizens there. It can no longer follow the old diplomatic strategy of keeping a low profile and keeping business and politics separate. China has learned from crises in Libya and Sudan and changed its policy from non-intervention to active mediation, supporting UN sanctions, contributing to UN peacekeeping missions and securing peacekeeping to protect its oil interests. Doubts remain both within the GCC and in Chinese policymaking circles as to what extent China should be strategically involved in the Gulf, and China does not seek to challenge or replace the US as the security provider of the Middle East. However, there is no doubt that active pragmatism has become China's guiding diplomatic strategy and that we will see more political and strategic activities from China in the region. [...]
Keywords: 300; Danish and European foreign policies; Defense and security policy; Diplomacy and International Organisation; Oil; gas and minerals; The Middle East & North Africa; IranUnited States; China